EXPERIMENTAL STUDY OF THERMAL AND STRAIN FIELDS DURING DEFORMATION OF EN ENCHELON FAULTS AND ITS GEOLOGICAL IMPLICATIONS - Ma Jin; Ma Shaopeng; Liu Liqiang; Liu Peixun (Геодинамика и тектонофизика)
The article presents results of experimental studies using a bi-axial servo-control system to apply load on samples with extensional and compressional en echelon faults. During the experiments, variations of temperature and thermal images were recorded synchronously by a multi-path contact-type thermometric apparatus and a thermal image system, respectively. A digital CCD camera was employed to synchronously collect images of specimens’ surfaces. The digital speckle correlation method (DSCM) was utilized to analyze the images and to define displacements and strain fields. Our experimental results show that temperature fields have clear responses to opposite stress states in the jog areas of both types of the en echelon faults. Prior to failure of the jog area, its temperature is the highest at the compressional en echelon faults and the lowest at the extensional en echelon faults. Records by DSCM give evidence that mean strain of the jog area is the highest at compressional en echelon faults and the lowest at the extensional en echelon faults. It is revealed that deformation of the en echelon faults occurs in two stages, developing from stress build-up and fault propagation in the jog area to unstable sliding along the fault. Correspondingly, the mechanism of heating-up converts from strain heating into friction heating. During the period of transformation of the temperature rising mechanism, three events are observed in the jog area and its vicinity. Analyses of our experimental results demonstrate that variations of temperatures in the jog area can be indicative of fault sliding and suggest sliding directions. Observations and studies of temperature changes during transformation of the temperature rising mechanism at sensitive portions of faults are of great importance for early detection of precursors of unstable slip on active faults.